Pengembangan Tracking Pole Sebagai Tongkat dan Alat Penjepit Sampah bagi Pendaki Gunung - Danar Husain Hidayat; Lorensius Anang Setiyo Waloyo; Vinsensius Widdy Tri Prasetyo (Jompa Research and Development, 2023)
The increase in the number of mountain climbers has an impact on increasing the volume of rubbish along the climbing route which results in damage to the natural scenery on the climbing route, pollution of water sources, and changes in eating behavior patterns in animals. Trash handling on climbing routes has been carried out by providing sanctions for climbers who do not bring rubbish down to several base camps. The process of picking up climbers' rubbish experienced several obstacles, including: picking up dirty rubbish with unhygienic hands, limited water to wash their hands after picking up rubbish, difficulty for climbers picking up rubbish while wearing large bags, and rubbish on the edge of cliffs which endangered climbers. The aim of this research is to design the development of a tracking pole as a trash clamp tool for mountain climbers. The product development design for this research uses product development theory according to Ulrich which is divided into several phases, namely: planning phase, concept development phase, system level design phase, detailed design phase, testing and improvement phase, and product launch phase. This research is limited to the testing phase. The designed tracking pole is a tool that is simple and easy to use, as a stick and also a tool for collecting rubbish when climbers are climbing, a comfortable tool. The designed tracking pole was well received by climbers. This is shown in the panelists' responses after using the tracking pole during technical testing of the tool.